Parental conscription and cumulative adverse experiences in war-affected children and adolescents and their impact on mental health: a comment following Russia's invasion of Ukraine in 2022 - Katrin Erlewein; Emily Gossmann; Jörg M. Fegert (BMC, 2024)
Abstract Background With Russia's invasion of the Ukraine on February 2022, Ukrainian children and adolescents have been exposed to several stressful life events. In addition to the confrontation with war, flight and parent-child separation due to flight and forced displacement, the majority underwent another challenge at the initial phase of the war: the fatherly separation due to conscription. Main body In the literature, the negative effects of exposure to war and flight/refuge, parent-child separation due to flight or forced displacement and parental deployment are well established. In the context of self-experienced war, the effects of parent-child separation caused by compulsory military service have not yet been sufficiently taken into account. However, the findings of the literature on the impact of these events on the mental health of children and adolescents show that they are at high risk for developing numerous psychological and behavioral problems. Conclusion As children's and adolescents' mental health might be severely affected by war and its consequences, interventional programs that address the special needs of those children and adolescents are crucial.